FORMAL POLITICAL OATHS (Scientific journal of the Fergana State University, 2024)
In the article, the structural and compositional structure of the oath text takes a special place in the study of the general aspect of the oaths of the field, for the oaths of this style, the textual structure of the oath of office, which is part of the field oath, is in a monologic form, and the speaker speaks it orally and to be expressed in writing, its textual compositional structure will be three-level. The three-stage text is monologic in the size of a micromatte, and its first stage, that is, the formative part, is the mode of the sentence. In it, the addressee is expressed through the pronoun/I, after this pronoun, the full name of the speaker is given, and the sentence swear by Almighty God is considered a special faith indicator that shows the belief in the speakerʼs speech. opinions are expressed.